Le Peinture. - Chan, Yin Fong. (2013)
Le Peinture, which means ‘the painting’ in French, is a short experimental animation film by two NTU ADM students, Chan Yin Fong and Huang Yaohui, for their Final Year Project. Hans Bacher aided in the pre-production process exploring on the use of non photorealistic rendering techniques, and Ishu Patel guided the entire production stages throughout, providing much valued support and feedback. Dennis Trier from Germany composed the music.